Effectiveness of a tailored intervention to reduce antibiotics for urinary tract infections in nursing home residents: a cluster, randomised controlled trial. Issue 11 (November 2021) - Arnold, Sif Helene; Nygaard Jensen, Jette; Bjerrum, Lars; Siersma, Volkert; Winther Bang, Christine; Brostrøm Kousgaard, Marius; Holm, Anne
Summary: Background: When suspecting a urinary tract infection (UTI), the nursing home staff contacts a physician with clinical information on behalf of the resident; hence, poor understanding of UTI or a lack of clinical communicative skills can cause overtreatment with antibiotics. We investigated whether a tailored intervention that improves knowledge about UTI and communication skills in nursing home staff influences antibiotic prescriptions for UTI. Methods: This open-label, parallel-group, cluster randomised controlled trial was done at 22 participating nursing homes in Denmark. Patients were eligible if they were nursing home residents aged 65 years or older, had the nursing home listed as their permanent address, and resided in a living space designated for those with dementia or somatic health-care needs. We included nursing homes that were not participating in other UTI projects and those in which staff were present at all hours. Using computer-generated random numbers and stratification by municipality, a statistician randomised the nursing homes (1:1) to receive either interactive educational sessions and use of a dialogue tool or to continue standard practice. The statistical analysis was blinded. Staff attended 75 min sessions over 8 weeks to learn how to distinguish between UTIs and asymptomatic bacteriuria, evaluate non-specific symptoms, and use the dialogue tool. The primary outcome was the number of antibiotic prescriptions for acute UTI per resident per days at risk, defined as the number of days the resident had been present at the nursing home during the trial period. The trial is registered at ClinicalTrials.gov, NCT03715062 . Findings: Between June 1, 2017, and June 1, 2018, 22 of 68 invited nursing homes were recruited. Of 22 randomised nursing homes (n=1625 residents), 11 received the intervention (770 [92·2%] of 835 allocated residents) and 11 were in the control group (705 [89·2%] of 790 allocated residents). The standardised number of nursing home staff was 572 in the intervention group and 535 in the control group. All nursing homes completed the trial. 65 residents were excluded from data collection in the intervention group and 85 were excluded in the control group. 1470 residents (intervention n=765; control n=705) were analysed for the primary endpoint. The number of antibiotic prescriptions for UTI per resident was 134 per 84 035 days at risk in the intervention group and 228 per 77817 days at risk in the control group. The rate ratio (RR) of receiving an antibiotic for UTI was 0·51 (95% CI 0·37–0·71) in the unadjusted model and 0·42 (0·31–0·57) in the adjusted model. Of 140 diary entries of suspected UTIs, no deaths were reported. 421 (28·5%) of 1475 residents were admitted to hospital. The risk of all-cause hospitalisation increased in the intervention group (adjusted model RR 1·28, 95% CI 0·95–1·74), whereas all-cause mortality was lower in the intervention group (0·91, 0·62–1·33). Interpretation: The intervention effectively reduced antibiotic prescriptions and inappropriate treatments for UTI without substantially influencing all-cause hospitalisations and mortality. Funding: Danish Ministry of Health and the Velux Foundation.